Effectiveness of Reuse, Reduce, and Recycle Program Socialization in the Campus Environment - Rahmadina, Nurul; Syarifuddin, Achmad; Trisiah, Anita (Journal of Geosciences and Environmental Studies, 2024)
This research has a background problem which is seen from the campus environment, which is a densely populated social environment and the crowded traders in the campus environment, which makes the campus environment always creates waste, while UIN Raden Fatah Palembang is committed to becoming a green campus that is environmentally friendly and waste-free. The EcoGreen Campus Team of UIN Raden Fatah Palembang makes the Reuse, Reduce, and Recycle program and conducts socialization in the campus environment. This is the background of this study where researchers want to know whether the socialization carried out by the EcoGreen Campus Team of UIN Raden Fatah Palembang is running effectively. The theories used in this thesis are Flow Theory and SWOT Theory. The qualitative research method uses Miles and Huberman's data analysis techniques. The data sources of this research amounted to 11 people. The author gets the data from interviews, observation, and documentation. This study's results describe three communication flows used in socializing the Reuse, Reduce, and Recycle program: One-Step Flow Communication, Two-Step Flow Communication, and Multi-Step Flow Communication. There are also obstacles in the faculty environment when conducting socialization. Socialization is adequate for several forms of socialization, such as direct and socialization, using various media. In contrast, socialization through the Faculty has not run well, so it can be considered ineffective.